MENINGKATKAN PENGAMBILAN KEPUTUSAN MELALUI VIDEO PEMBELAJARAN BILINGUAL DENGAN CAPCUT - Ismi, Ismi Putri Intan; Netriwati; Salsabila; Fadly Nendra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This development research aims to develop a bilingual learning video based on CapCut to improve valid and effective decision making to facilitate students and educators in the learning process. This study uses a research and development type of research with the DDDE (Decide, Design, Develop, and Evaluate) model. The data analysis techniques used are small-scale validity tests and N-Gain tests. The test subjects in this study were semester 2 students of the Mathematics Education Study Program, Faculty of Tarbiyah and Teacher Training, Raden Intan State Islamic University, Lampung. The results of the validity test on a small scale show that the instruments used are valid and reliable. The assessment of the effectiveness test using N-Gain on the test obtained a score of 0.439 with the criteria of